Effect of stabilizer pressure biofeedback on post-thyroidectomy neck pain in postmenopausal women: a randomized controlled trial - Elham S Hassan; Afaf M. Botla; Marian Y. Abdou; Abdel Hamid A. Attalla; Khadra Mohamed Ali; Shreen Rashad Aboelmaged (Physiotherapy Quarterly)
Introduction To investigate the effect of stabilizer pressure biofeedback on post-thyroidectomy neck pain, disability, endurance capacity of deep cervical flexors (DCFs), and cervical range of motion (ROM) in women after menopause.